PENGARUH TERAPI GAME PUZZLE TERHADAP KECEMASAN PADA ANAK SAAT PENYUNTIKAN ANESTESI SIRKUMSISI DI YAYASAN ISHAK AL- HIJRAH AMBON - Sudin Kelilawa; Abdul Thalib (Pasapua Health Journal, 2022)
Introduction : circumcision or circumcision is something that is mandatory for the Muslim community which is the sunnah of the apostle in worship as one of the requirements for tahara (cleanliness) in performing prayer services. Objective: To determine the effect of puzzle game therapy on anxiety in children when injecting circumcision anesthesia at the Ishak Al-Hijrah Ambon foundation in 2021. Method: This type of research uses a pre-experimental design (one group pre-test-posttest), with a sample of 15 respondents. The sampling technique is by accidental sampling. Data analysis used the Wilcoxon test. Results: Anxiety pre-test before doing puzzle game therapy in children when injecting circumcision anesthesia at the Ambon Ishal Al-Hijrah Foundation obtained from 15 respondents, 12 respondents with moderate anxiety (80%), 3 respondents with mild anxiety (20%). Anxiety post-test after giving puzzle games to circumcision patients at the Ishak Al-Hijrah Ambon Foundation, obtained from 15 respondents, 11 respondents with mild anxiety (73.3%), 4 respondents with no anxiety (26.7%). The results of the study based on the Wilcoxon signed ranked test statistical test found a significant p-value = .195 where the p-value <.227, it means that there is a significant effect between the effect of puzzle game therapy on anxiety in children when injecting circumcision anesthesia at the Ishak Al- Hijrah Ambon in 2021. Conclution : Based on the results of the study, it was found that there was an effect of puzzle game therapy on anxiety in children when injecting circumcision anesthesia at the Ishak Al-Hijrah Ambon Foundation in 202.